Effect of adapted motorized ride-on toy use on developmental skills, quality of life, and driving competency in nonambulatory children age 9–60 months. Issue 1 (2nd January 2023) - Arps, Kara; Darr, Nancy; Katz, Jamie
ABSTRACT: Adapted motorized ride-on toys (AMTs) provide a feasible option for independent mobility in children with physical limitations. This study explores implications of AMT use on developmental domains and participation in daily activities. It also pilots the Power Mobility Skills Checklist (PMSC) for assessment of AMT operation competency. Nine nonambulatory children, ages 10–35 months, completed a 16-week AMT intervention. The Battelle Developmental Inventory-2 (BDI-2) and Assessment for Life Habits for Children (Life-H) were completed pre- and poststudy to evaluate developmental skills and participation in daily activities. The PMSC was completed at 2-week intervals to assess AMT driving ability. PMSC scores improved significantly for all participants across the intervention. BDI-2 developmental quotients demonstrated clinically significant gains in motor, cognitive, adaptive, communication, and personal-social domains, which varied between participants. Life-H changes were not significant. Improvements in PMSC change scores were associated with more total AMT sessions and increased BDI-2 gains. The PMSC may be effective for obtaining quantitative data on AMT operation and sensitive for assessing change in driving competency.